How does Job Satisfaction Affect the Job Performance of Employees? - Lam, Kah Yee; Kee, Daisy Mui Hung; Kumar C, Akshay; Jain, Ashi; Pandey, Rudresh; Singh, Ashvinderjit; Chua, Chuan Rou; Chia, Jian Wei; Arenas, Venus Toro; Lopez, Carolina Ardila; Restrepo, Camilo Alberto Perez (Asia Pacific Journal of Management and Education (APJME), 2020)
The paper seeks to evaluate OYO Homes & Hotels, an Indian Hotel chain that holds the position of the third-largest hospitality chain in the world. The purpose of this paper is to evaluate how job satisfaction affects the performance of employees in OYO as a service provider company. The research will be based on secondary information gathered from databases, Internet and relevant information provided on OYO's official website. To fulfill the objective, the project aims to analyze the employees' main causes of job satisfaction, strategies in dealing with job dissatisfaction, and changes in performance. Finally, with the analysis, the project will establish recommendations for OYO to maximize employee performance in relation to job satisfaction.